Occupational Therapists’ Perspectives for Promoting Fieldwork Experiences in Private Practice - Drynan, Donna Patricia; Boniface, Jeffrey; Olsen, Jenna (International Journal of Practice-based Learning in Health and Social Care, 2024)
Limited private practice fieldwork opportunities exist in Canadian occupational therapy (OT) education programs, in comparison to public health opportunities. This gap must be addressed to ensure students have opportunities to gain experience in the private sector. There are limited qualitative studies in occupational therapy that identify strategies to encourage occupational therapists to offer placements in this area. This qualitative study explored the experiences and perspectives of occupational therapists working in private practice and their motivations and uncertainty to participate in occupational therapy student education. Strategies to best support fieldwork educators as well as opportunities to advance student preparation for private practice placements, were uncovered. Using purposive sampling, nine occupational therapists working in private practice with or without fieldwork educator experience, participated in semi-structured interviews. Phenomenology was used to analyze data and determine emergent themes. Four themes emerged that highlight key considerations for occupational therapists hosting students in private practice. Motivations and hesitations for hosting students were uncovered. Strategies which can be used to directly support private practice occupational therapists and facilitate student learning at the university level prior to fieldwork placements in this area, were revealed. It is imperative to understand occupational therapist’s perspectives when hosting students as well as hesitations for not hosting students in private practice. These findings contribute practical and viable approaches that can be utilized by education programs and the private sector, to ensure mutually beneficial partnerships.